2009
DOI: 10.4306/pi.2009.6.4.286
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Cognitive Function in Schizophrenia with and without Obsessive Compulsive Disorder

Abstract: ObjectiveWe investigated the neurocognitive deficits in schizophrenic patients with and without obsessive-compulsive disorder (OCD).MethodsWe grouped 27 patients as either obsessive-compulsive or non-obsessive-compulsive based on the presence of OCD. The two groups completed the Yale-Brown Obsessive-Compulsive Scale (Y-BOCS), Positive and Negative Symptom Scale (PANSS), and Hamilton Depression Scale. The intelligence quotient (IQ) was tested using the Korean Wechsler Adult Intelligence Scale. The memory quotie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 18 publications
3
16
0
3
Order By: Relevance
“…Th ese differen t findin gs m ay be related to th e varying study population and the diverse n ature of obsessivecom pulsive sym ptom s in sch izophren ic illn ess. In addition, type and dosage of an tipsychotics w ere not evenly distributed am on g groups according to th e presence of obsessive-com pulsive sym ptom s in m any previous studies (Rajkum ar et al, 2008;Lee et al, 2009;Tum kaya et al, 20 09;Ow ashi et al, 2010;Sch irm beck et al, 2013a). Particularly, previous findings th at populations w ith obsessive-compulsive symptoms are more likely to have longer duration of illn ess or take clozapin e, w h ich is m ain ly u sed in treatm ent refractory patients, m ay confoun d study results w ith poorer outcom e (Patel et al, 2010;Schirm beck et al, 2013a).…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Th ese differen t findin gs m ay be related to th e varying study population and the diverse n ature of obsessivecom pulsive sym ptom s in sch izophren ic illn ess. In addition, type and dosage of an tipsychotics w ere not evenly distributed am on g groups according to th e presence of obsessive-com pulsive sym ptom s in m any previous studies (Rajkum ar et al, 2008;Lee et al, 2009;Tum kaya et al, 20 09;Ow ashi et al, 2010;Sch irm beck et al, 2013a). Particularly, previous findings th at populations w ith obsessive-compulsive symptoms are more likely to have longer duration of illn ess or take clozapin e, w h ich is m ain ly u sed in treatm ent refractory patients, m ay confoun d study results w ith poorer outcom e (Patel et al, 2010;Schirm beck et al, 2013a).…”
Section: Introductionmentioning
confidence: 79%
“…A recent study w ith a large sam ple including unaffected relatives did n ot fin d a clear association between obsessive-com pulsive sym ptom s and cognitive perform ance, whereas patients with schizophrenia and obsessive-com pulsive sym ptom s displayed a m ore severe clinical profile (Meijer et al, 2013). In contrast, a few studies reported that com orbid obsessivecom pulsive sym ptom s w ere associated w ith better neurocognitive functioning in schizophrenia patien ts w ith less than 10 years m ean illn ess duration an d proposed th at obsessive-com pulsive sym ptom s m ay have a protective effect in the early stages of schizophrenia (Borkowska et al, 2003;Lee et al, 2009). How ever, th ose studies used sm all sam ples w ith few er than 30 patients w ith sch izophren ia.…”
Section: Patients W Ith Doio 5yearsmentioning
confidence: 99%
See 1 more Smart Citation
“…While some studies found OCS to be linked to cognitive deficits , others found no evidence for cognitive differences between schizophrenia patients with or without co‐occurring OCS . Some studies even reported better performance of the comorbid group within patients with schizophrenia or in the at risk mental state of psychosis .The inconsistency of results may partly be explained by the cross‐sectional nature of most studies. To the best of our knowledge, only two studies prospectively assessed neurocognitive functioning in comorbid samples over time.…”
Section: Introductionmentioning
confidence: 96%
“…Findings have been contradicting. Whereas some investigations did not find any significant differences (Hermesh et al, 2003; Whitney et al, 2004; Öngür and Goff, 2005; Tumkaya et al, 2009; Tiryaki and Ozkorumak, 2010; Achim et al, 2011; Meijer et al, 2013), others even suggested that OCS may be associated with better cognitive abilities (Lee et al, 2009; Borkowska et al, 2013), especially in the prodromal states of schizophrenia (Van Dael et al, 2011; Fontenelle et al, 2012; Hur et al, 2012; Zink et al, under review). Most results, however, showed more pronounced deficits in the described domains of executive functioning (Hwang et al, 2000; Lysaker et al, 2002, 2009), cognitive flexibility (Kumbhani et al, 2010; Patel et al, 2010), and also delayed visual memory (Berman et al, 1998; Schirmbeck et al, 2011).…”
Section: Clinical Presentation and Explanatory Conceptsmentioning
confidence: 99%